The Parameters Comparison of the “Starlink” LEO Satellites Constellation for Different Orbital Shells - Cakaj, Shkelzen (Frontiers in Communications and Networks, 2021)
Communications-integrated satellite-terrestrial networks used for global broadband services have gained a high degree of interest from scientists and industries worldwide. The most convenient structures for such use are low Earth orbit satellites, since they fly closer to the Earth compared to the other orbits, and consequently provide significantly lower latency, which is essential for reliable and safe communications. Among these efforts is the Starlink satellites constellation, developed and partly deployed by the United States Company SpaceX. The constellation is planned to be organized in three spatial shells, each of them made up of several hundreds of small-dimensioned and light-weighted low Earth orbit specially designed satellites to provide broadband services, intending to offer global Earth coverage through their interoperability, combined also with the ground stations as a part of the satellite-terrestrial integrated network. By October 24, 2020, 893 satellites are situated in orbit of altitudes of 550 km under different inclinations, determining the first Starlink orbital shell. Two next generations are planned to be situated at altitudes of 1,110 and 340 km, to complete the appropriate infrastructure of three Starlink satellite shells, toward a global presence of broadband internet services. These three orbital shells offer different space views seen from the ground station (user) because of their different altitudes, thus in this paper a few parameters which describe the satellite’s behavior considered from the ground station’s (user’s) point of view are compared. These parameters in fact stem from the space orbital parameters and are defined as: horizon plane wideness, slant range, latency, and coverage area. A comparison is given for the three Starlink orbit layers, with identification of appropriate drawbacks and advantages as performance indicators. By the end, these parameters are applied to geometrically interpret and confirm the handover process among satellites. This paper may serve to highlight the new challenges of the satellite-terrestrial integrated network, providing some theoretical analysis and performance comparisons for the satellites in different orbit layers seen from the ground station (user) perspective.